Neonatal and Juvenile Ocular Development in Göttingen Minipigs and Domestic Pigs: A Histomorphological and Immunohistochemical Study. Issue 6 (November 2020) - Vrolyk, Vanessa; Desmarais, Marie-Josée; Lambert, Daniel; Haruna, Julius; Benoit-Biancamano, Marie-Odile
Pigs are considered one of the relevant animal models for ocular research as they share several histological and anatomical similarities with the human eye. With the increasing interest in juvenile animal models, this study aimed to describe the postnatal development of ocular structures in 16 Göttingen minipigs and 25 F2 domestic pigs, between birth and 6 months of age, using histopathology and immunohistochemistry against Ki-67, caspase-3, calbindin, glial fibrillary acidic protein, rhodopsin, and synaptophysin. All ocular structures in both pig breeds were incompletely developed at birth and for variable periods postnatally. Noteworthy histological features of immaturity included vascularization in the corneal stroma in neonatal Göttingen minipigs, increased cellularity in different substructures, remnants of the hyaloid vasculature, short and poorly ramified ciliary body processes, and a poorly developed cone inner segment. Increased cellular proliferation, highlighted by abundant Ki-67 immunolabeling, was observed in almost all developing structures of the pig eye for variable periods postnatally. Apoptosis, highlighted with caspase-3 immunolabeling, was observed in the retinal inner nuclear layer at birth and in the regressing hyaloid vasculature remnants. Immunohistochemistry against rhodopsin, synaptophysin, and calbindin demonstrated the short size of the developing photoreceptors and the immature cone inner segment morphology. Calbindin labeling revealed significant differences in the amount of positively labeled cone nuclei between the retinal area centralis and the non–area centralis regions. The elongation of Müller cell processes in the developing retina was shown with glial fibrillary acidic protein. In both pig breeds, the eyes reached histomorphological and immunohistochemical maturity at 6 months of age.